2016
DOI: 10.7717/peerj.2410
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low genetic variability within and among locations of the greenfish holothurianStichopus chloronotusBrandt, 1835 in Okinawa, Japan

Abstract: The greenfish sea cucumber Stichopus chloronotus is an economically and ecologically important sea cucumber species throughout its range. This species is widely distributed, inhabiting coral reefs of the Indo-Pacific Ocean. Our study evaluated population genetic structure and levels of genetic diversity in southern Japan. A total of 180 individuals were collected from eight locations from Okinawa and Okinoerabu Islands and sequenced using mitochondrial 16S ribosomal DNA (16S) and nuclear histone H3 (H3) gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…2B). Due to recent commercial pressure and reported large drops in abundances of some echinoderms (e.g., annual Okinawa Prefecture harvest of Tripneustes gratilla sea urchin from >700 t in 1976 to <50 t in late 1990s (Kakuma, 2003), see also Soliman, Fernandez-Silva & Reimer (2016); Soliman et al (2016)), it is clear that more research is urgently needed in other sub-regions. Hughes, Bellwood & Connolly (2002) suggested nearly two decades ago that more work is needed on understudied small and cryptic coral reef taxa in understudied locations, and this is still true for the RYS.…”
Section: Discussionmentioning
confidence: 99%
“…2B). Due to recent commercial pressure and reported large drops in abundances of some echinoderms (e.g., annual Okinawa Prefecture harvest of Tripneustes gratilla sea urchin from >700 t in 1976 to <50 t in late 1990s (Kakuma, 2003), see also Soliman, Fernandez-Silva & Reimer (2016); Soliman et al (2016)), it is clear that more research is urgently needed in other sub-regions. Hughes, Bellwood & Connolly (2002) suggested nearly two decades ago that more work is needed on understudied small and cryptic coral reef taxa in understudied locations, and this is still true for the RYS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that S. chloronotus is also overharvested in East Africa and the Pacific ( Pirog et al, 2019 ). As well, based on extremely low mitochondrial genetic diversity, it has been suggested this species has experienced high anthropogenic pressure around Okinawajima Island ( Soliman et al, 2016 ). In the present study, the low population density of S. chloronotus compared to previous studies (0.04 ind/m 2 maximum in current study; 0.09 ind/m 2 at Mauritius ( Lampe, 2013 ); 1.5–3.6 ind/m 2 at La Réunion ( Kohler, Gaudron & Conand, 2009 )) may also show such impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that genus Stichopus widely distribute across most of the tropical Indo-Pacific region, from the Western Indian Ocean to the Central Pacific, and from southern Japan to northern Australia. This genus can observe from shallow to deep waters from the intertidal zone to depths of 30 m on coral reef flats and slopes in dense numbers, of which greenfish sea cucumber S. chloronotus is an economically and ecologically important species [12,20]. In this survey, vertical distribution of sea cucumbers is different among species e.g.…”
Section: Oceanography and Fisheries Open Access Journalmentioning
confidence: 99%